Apparent reduction in heart rate during oviposition revealed by non-invasive heart rate monitoring of gravid loggerhead turtles - Narazaki, Tomoko; Mori, Masanori; Matsuzawa, Yoshimasa; Saito, Ayaka; Kinoshita, Chihiro; Kurita, Masanori; Matsumiya, Kensuke; Okada, Hikari; Sakamoto, Kentaro Q. (Frontiers in Physiology, 2025)
Reproductive processes place significant physiological demands on animals, often accompanied by hormonal and neural changes. In this study, we examined changes in heart rate of gravid loggerhead turtles (Caretta caretta) during nesting activities on the beach, especially during egg-laying phase. To examine heart rate throughout the nesting activities, non-invasive electrocardiogram (ECG) loggers and accelerometers were deployed on five gravid females. Heart rate increased markedly upon beach landing and remained elevated during most nesting phases. However, a significant decrease in heart rate, often accompanied by increased RMSSD, was observed during egg-laying, suggesting parasympathetic nervous system dominance during this phase. This pattern is similar to observation reported in other species (e.g., horses and chum salmon), where bradycardia during reproductive events is associated with elevated parasympathetic tone. Our study reported an apparent reduction in heart rate during oviposition, which reflects the physiological mechanisms underlying nesting activities in sea turtles, and suggest that external stressors disrupting parasympathetic activity may reduce egg-laying success.